Effect Of Hormonal And Non-Hormonal Treatment On Reproductive Efficiency And Plasma Progesterone, Biochemical And Macrominerals Profile In Postpartum Anoestrus Buffaloes - Parmar, K.H.; Shah, R.G.; Tank, P.H.; Dhami , A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Fifty two postpartum anoestrus Surti buffaloes selected through glynaeco-clinical examinations in three village co-operative societies of Panchmahal district were randomly divided into four groups. Group-A (n=14) was treated with oral supplementation of Chelated mineral mixture @ 30 g/day/ animal for one month, Group-B (n=14) with Inj. inorganic phosphorus and Inj. vitamin AD3E 10 ml each, im at weekly interval for three consecutive week, Group-C (n=12) with Inj. GnRH (Receptal) 5.0 ml, im once and Group-D (n=12) served as untreated control. The effect of above treatments on reproductive efficiency and plasma profile of progesterone and various biochemical and macro minerals was studied at pre-treatment, at induced oestrus and 22nd day post-AI. Significantly higher oestrus induction response (83.33%), the highest conception rate (80.00 %) and reproductive efficiency (66.66 %) were observed for group-C GnRH treated buffaloes followed by group-B and A, and the values were lowest in control group-D. The mean plasma progesterone (ng/ml) levels were significantly (P
Keywords: Postpartum Anoestrus Buffaloes; Treatment regimens; Reproductive efficiency; Plasma Progesterone; Biochemical profile; Macro-minerals